A Comprehensive Analysis and Research on the Factors Affecting the Growth of Rural Trade in Cultural Communities - Maviya, Arnold; Ndlovu, Sithembile (Journal of Global Economy, Business and Finance, 2024)
This article analyzes the elements that impact the stages of rural retailing development in the Hwange villages, namely in the areas of Jambezi, Mununa, Milonga, Ndlovu, Chikhanda, Mashake, and Monde. The study used a quantitative technique with a sample size of 400 people, recruited by stratified random sampling. The data analysis was performed using SPSS version 26.0. The survey's main findings reveal that rural residents have a preference for firms that value outstanding customer service and offer a broader range of recreational choices. Furthermore, the condition of road networks was recognized as a crucial element impacting the operational effectiveness of rural businesses. The presence of essential services such as water and electricity was discovered to have a substantial influence on the condition of the retail sector. The paper provides numerous recommendations based on the findings. The implementation of these recommendations is anticipated to stimulate economic expansion, boost living standards, and promote overall welfare in rural regions. By effectively dealing with the highlighted causes, the communities in Hwange have the opportunity to experience positive changes in their retailing industry, which will result in sustainable development and an enhanced quality of life.